2018
DOI: 10.1111/pcn.12788
|View full text |Cite
|
Sign up to set email alerts
|

Exome sequencing in families with severe mental illness identifies novel and rare variants in genes implicated in Mendelian neuropsychiatric syndromes

Abstract: Aim Severe mental illnesses (SMI), such as bipolar disorder and schizophrenia, are highly heritable, and have a complex pattern of inheritance. Genome‐wide association studies detect a part of the heritability, which can be attributed to common genetic variation. Examination of rare variants with next‐generation sequencing may add to the understanding of the genetic architecture of SMI. Methods We analyzed 32 ill subjects from eight multiplex families and 33 healthy individuals using whole‐exome sequencing. Pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 69 publications
0
18
0
1
Order By: Relevance
“…rs751524528 (p.A80V) is a benign non‐synonymous mutation (according to Polyphen2) in a 31‐year‐old female affected by adult‐onset schizoaffective disorder (bipolar type) without developmental delays, mental retardation, and learning disabilities (Xu et al, 2011). rs775793924 (p.R168W) is a rare SNV defined by authors as a «non‐synonymous damaging strict and disruptive» variant and was found in a multiplex family with subjects affected by bipolar disorder or SSD with no phenotypic description (Ganesh et al, 2019). Finally, an epigenome‐wide significant ( p < 1.7 × 10 −8 ) association for phonemic verbal fluency (cg12507869, p = 2.5 × 10 −9 ) was found in an epigenome‐wide association study.…”
Section: Discussionmentioning
confidence: 99%
“…rs751524528 (p.A80V) is a benign non‐synonymous mutation (according to Polyphen2) in a 31‐year‐old female affected by adult‐onset schizoaffective disorder (bipolar type) without developmental delays, mental retardation, and learning disabilities (Xu et al, 2011). rs775793924 (p.R168W) is a rare SNV defined by authors as a «non‐synonymous damaging strict and disruptive» variant and was found in a multiplex family with subjects affected by bipolar disorder or SSD with no phenotypic description (Ganesh et al, 2019). Finally, an epigenome‐wide significant ( p < 1.7 × 10 −8 ) association for phonemic verbal fluency (cg12507869, p = 2.5 × 10 −9 ) was found in an epigenome‐wide association study.…”
Section: Discussionmentioning
confidence: 99%
“…These rare variants may be shared within family members. 6 Hence, the study of rare variants of moderate-to-large effects becomes important, as they may highlight the dysfunction of disease-associated pathways.…”
Section: Case Presentationsmentioning
confidence: 99%
“…As described in our previous study 59 , whole exome sequencing was carried out on the Illumina Hiseq NGS platform with libraries prepared using Illumina exome kits. Reads were aligned with the reference human genome hg19 using the Burrows-Wheeler algorithm tool (https://academic.oup.com/bioinformatics/article/25/14/1754/225615).…”
Section: Sequencing and Quality Controlmentioning
confidence: 99%